Characterization of the prokaryotic community and analysis of the exopolysaccharidic matrix of Biological soil crust of High Arctic - MUGNAI, GIANMARCO; ROSSI, FEDERICO; ADESSI, ALESSANDRA; Mascalchi, C.; Ventura, S.; DE PHILIPPIS, ROBERTO (Tubingen University, 2015)
Biological soil crusts in Svalbard Islands